Cross-cultural generalizability of social and dimensional comparison effects on reading, math, and science self-concepts for primary school students using the combined PIRLS and TIMSS data. (December 2018) - Guo, Jiesi; Marsh, Herbert W.; Parker, Philip D.; Dicke, Theresa
Abstract: Previous cross-cultural studies of social and dimensional comparison processes forming academic self-concepts (the big-fish-little-pond effect (BFLPE) and Internal-external frame-of-reference (I/E) models) have mostly been based on high-school students and two subject domains. Our study is the first to test the cross-cultural generalizability of both comparison processes across reading, mathematics, and science by combining of the TIMSS and PIRLS 2011 databases (15 OECD countries, 67, 386 fourth-graders). Consistent with the I/E model, high achievement in mathematics/reading had positive effects on self-concept in the matching domain but negative effects in the non-matching domain. Extending the I/E model, students engaged in assimilating comparisons between science and reading (i.e., achievement in one subject had positive effects on self-concept in the other) but contrasting comparisons between mathematics and science. Strong BFLPEs (negative effects of class-average achievement on self-concept) were found for mathematics but were smaller for reading and science. The results generalized well across all countries. Highlights: The combined TIMSS and PIRLS databases were used to test formation of self-concept. We tested BFLPE and DCT across reading, math, and science for primary students. Students engaged in contrasting and assimilating comparisons across three domains. Strong BFLPEs were found for math but were smaller for reading and science. The results generalized well across 15 OECD countries.